Pemberdayaan Kelompok Masyarakat Suryasari dalam meningkatkan pelayanan dan pemasaran Agrowisata Petik Belimbing melalui Model Eduwisata STAR (Sharing, Trying, and Adventuring) berbasis produk Nata de Averrhoa carambola - Hesty Puspita Sari; Mar’atus Sholihah; Abdi Pandu Kusuma (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
Karangsari has a starfruit picking agrotourism which is managed by the Suryasari community service. The Agrotourism of starfruit provided visitors a very simple and less varied service. The most common package taken by visitors is the starfruit picking package. Meanwhile, the implementation of the education package is still not optimal because the education provided is only a brief explanation about the cultivation of star fruit that is given while walking around the garden while picking the starfruit. Priority partners problems arises are less than optimal services in Agrotourism, especially in education packages, lack of partner skills in processing star fruit, especially star fruit that is overripe or slightly defective (damaged), and not yet optimal digital marketing so that the number of visitors is still limited from the area. local. The purpose of this activity is to empower the Suryasari community service in improving agro-tourism services and marketing through the product-based STAR edutourism model to improve tourism services in Karangsari Belimbing Picking Agrotourism. The methods applied in this activity include: (a) socialization and discussion about the product-based STAR edutourism model, (b) training on how to become an edutourism guide indoors and outdoors, (c) training on making nata de Averhoa carambola, (d) training in technical- digital marketing techniques, and (e) assisting partners in implementing product-based STAR edutourism packages to digital marketing. The results of this service could increase the partner's quality to become indoor and outdoor edutourism guides, increase the partner's ability to process starfruit into nata, and increase the partner's ability in digital marketing as shown by the results of partner responses to training activities that are quite good with 95% reaction level indicators, learning level 87%, behavior level 83%, and result level 80%. PkM activities also increase digital marketing activities by partners with the Karangsari Picking starfruit Agrotourism website. This activity has a positive impact on the Suryasari community service so that it is more qualified and able to provide maximum service for visitors to Karangsari starfruit picking agrotourism, Blitar, East Java.